PERSPEKTIF GONE THEORY DALAM DETERMINAN ACADEMICAL FRAUD - Fatimah, Fatimah; Saprudin, Saprudin; Yasin, Muhammad (Dinamika Ekonomi: Jurnal Ekonomi dan Bisnis, 2024)
Abstract, The phenomenon of academic fraud has become a problem in almost all countries around the world. It is an interesting yet threatening phenomenon in the academic education world because education, which is supposed to be a means to improve the quality of human resources, has instead become a hotbed of many fraudulent practices. Based on the phenomenon and research gaps in academic fraud studies, the researcher is interested in developing this research using the dimensions of the GONE theory as a differentiator from previous research. The GONE theory is often used to uncover corruption cases, so it is expected to serve as a basis for mitigation while exploring the causes of deviant behavior in the academic field conducted by accounting students in Banjarmasin. The research results show that X1 and X2 have an influence, while X3 and X4 do not. Greed (X1) and Opportunity (X2) influence academic fraud, whereas Need (X3) and Exposure (X4) do not influence academic fraud.